Comparative Proteome Profiling of Saliva Between Estrus and Non-Estrus Stages by Employing Label-Free Quantitation (LFQ) and Tandem Mass Tag (TMT)-LC-MS/MS Analysis: An Approach for Estrus Biomarker Identification in Bubalus bubalis - Singh, Laishram Kipjen; Pandey, Mamta; Baithalu, Rubina Kumari; Fernandes, Abhijeet; Ali, Syed Azmal; Jaiswal, Latika; Pannu, Suryaprakash; Neeraj,; Mohanty, Tushar K.; Kumaresan, A.; Datta, Tirtha K.; Kumar, Sudarshan; et al. (Frontiers in Genetics, 2022)
Accurate determination of estrus is essentially required for efficient reproduction management of farm animals. Buffalo is a shy breeder and does not manifest overt signs of estrus that make estrus detection difficult resulting in a poor conception rate. Therefore, identifying estrus biomarkers in easily accessible biofluid such as saliva is of utmost interest. In the current study, we generated saliva proteome profiles during proestrus (PE), estrus (E), metestrus (ME), and diestrus (DE) stages of the buffalo estrous cycle using both label-free quantitation (LFQ) and labeled (TMT) quantitation and mass spectrometry analysis. A total of 520 proteins were identified as DEPs in LFQ; among these, 59 and four proteins were upregulated (FC ≥ 1.5) and downregulated (FC ≤ 0.5) during E vs. PE, ME, and DE comparisons, respectively. Similarly, TMT-LC-MS/MS analysis identified 369 DEPs; among these, 74 and 73 proteins were upregulated and downregulated during E vs. PE, ME, and DE stages, respectively. Functional annotations of GO terms showed enrichment of glycolysis, pyruvate metabolism, endopeptidase inhibitor activity, salivary secretion, innate immune response, calcium ion binding, oocyte meiosis, and estrogen signaling. Over-expression of SERPINB1, HSPA1A, VMO1, SDF4, LCN1, OBP, and ENO3 proteins during estrus was further confirmed by Western blotting. This is the first comprehensive report on differential proteome analysis of buffalo saliva between estrus and non-estrus stages. This study generated an important panel of candidate proteins that may be considered buffalo estrus biomarkers which can be applied in the development of a diagnostic kit for estrus detection in buffalo.